A systematic review of collaboration and network research in the public affairs literature: implications for public health practice and research - Varda, Danielle; Shoup, Jo Ann; Miller, Sara (American journal of public health, 2012)
OBJECTIVES: We explored and analyzed how findings from public affairs research can inform public health research and practice, specifically in the area of interorganizational collaboration, one of the most promising practice-based approaches in the public health field. METHODS: We conducted a systematic review of the public affairs literature by following a grounded theory approach. We coded 151 articles for demographics and empirical findings (n = 258). RESULTS: Three primary findings stand out in the public affairs literature: network structure affects governance, management strategies exist for administrators, and collaboration can be linked to outcomes. These findings are linked to priorities in public health practice. CONCLUSIONS: Overall, we found that public affairs has a long and rich history of research in collaborations that offers unique organizational theory and management tools to public health practitioners.
Edition: 2011/11/28 Publisher: American Public Health Association
Keywords: L - english / inglês; collaboration / colaboração; health / saúde